2020
DOI: 10.1093/mnras/staa243
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the origin of the planetary debris surrounding ZTF J0139+5245 through rotational fission of a triaxial asteroid

Abstract: White dwarfs containing orbiting planetesimals or their debris represent crucial benchmarks by which theoretical investigations of post-main-sequence planetary systems may be calibrated. The photometric transit signatures of likely planetary debris in the ZTF J0139+5245 white dwarf system has an orbital period of about 110 days. An asteroid which breaks up to produce this debris may spin itself to destruction through repeated close encounters with the star without entering its Roche radius and without influenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…We have shown here that the survival timescales for spin discs are strongly dependent on the values of Rp and M disc , and can vary from seconds to about 1 Myr (despite some cold disc cases with small numbers of planetesimals where the survival timescales exceed this value). If the disc mass in ZTF J0139+5245 is 10 14 − 10 15 kg (Veras et al 2020a), then Fig. 5 demonstrates that the lifetime of this disc is at least hundreds if not thousands of years; only if the star was brighter would the disc be influenced by the Yarkovsky effect.…”
Section: Implications Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown here that the survival timescales for spin discs are strongly dependent on the values of Rp and M disc , and can vary from seconds to about 1 Myr (despite some cold disc cases with small numbers of planetesimals where the survival timescales exceed this value). If the disc mass in ZTF J0139+5245 is 10 14 − 10 15 kg (Veras et al 2020a), then Fig. 5 demonstrates that the lifetime of this disc is at least hundreds if not thousands of years; only if the star was brighter would the disc be influenced by the Yarkovsky effect.…”
Section: Implications Of Resultsmentioning
confidence: 99%
“…Makarov & Veras (2019) demonstrated the concept of YORP-less spin-up to destruction due solely to close passages with a white dwarf, and Veras et al (2020a) applied the idea to the ZTF J0139+5245 system, where the semimajor axis of the debris is just 0.42 au (Vanderbosch et al 2020). Veras et al (2020a) found that rotational fission could occur at separations up to 3R Roche across the progenitor density range of 1 − 8 g/cm 3 . We adopt max(ro) = 4.5R⊙ here for these discs, but acknowledge that spin discs may extend further pending future parameter space explorations.…”
Section: The Outer Radius Romentioning
confidence: 97%
See 3 more Smart Citations